Making occupations possible? A critical analysis of social assistance policy in Ontario - Peter, Nedra R (2018)
This thesis reports on a two-part study exploring the occupational possibilities of people receiving social assistance in Ontario. The research conducted in this thesis was guided by the research question: How does social assistance in the form of Ontario Works and the Ontario Disability Support Program influence occupational possibilities for adults living in poverty? Guided by a governmentality perspective, Laliberte Rudman (2010) proposes that social and political processes shape expectations and possibilities for occupations. Occupational possibilities refer to the occupations that are supported and promoted by various aspects of the broader systems and structures in which lives are lived (Laliberte Rudman, 2005, 2006). The first part of the study provides a narrative of five people receiving social assistance using critical narrative analysis (CNA). Critical narrative analysis combines hermeneutic phenomenology with critical theory following Ricoeur (Langridge, 2007). The narratives of participants are presented, followed by a thematic discussion of their experiences with social assistance. After using governmentality theory to interrogate the data, the participants’ responses demonstrated several tensions created by neoliberalism. These tensions are presented through three paradoxes: the Neoliberal Paradox, the Welfare-to-Work Paradox, and the Caseworker Paradox. In pursuing a critical analysis of policy in the second study, the WRP: What’s the Problem Represented to Be? approach (Bacchi, 2009) was completed. The policy of income exception or clawback was examined. Clawback was shown to be created to provide financial incentives to work while also reducing or deterring reliance on social assistance. However there are several important aspects of becoming self-sufficient which are silent including: work related expenses, housing, parental support, secondary education and basic human rights. The effects of clawback policy are also discussed. The two studies combined to show how social assistance recipients experience lack of opportunity and resources to make everyday choices and to have decision-making power as they participate in occupations. Occupational scientists may play a role in raising the consciousness about the concept of active citizenship and the need to acknowledge a wider range of occupations. This thesis includes recommendations that highlight the promotion of occupational justice for people reliant of social assistance